6 - x = 2(x - 6)
the first step, following PEMDAS, is to distribute the 2 to the inside of your parentheses:
6 - x = 2x - 12 ... subtract 2x
6 - 3x = -12 ... subtract 6
-3x = -18 ... divide by -3
x = 6 is the answer
Answer:
b/-7=4
b=4*-7
b= - 28
Step-by-step explanation:
If this helps you mark as brainlist.!
Answer:
Step-by-step explanation:
So
f(x) = -8x +11, for f(-4).
= -8(-4)+11
= 32 + 11
= 43
Answer:
option 4 ⇒ 236 lb.
Step-by-step explanation:
Best explanation of the question is as shown in the attached figure.
we will use the parallelogram method to calculate resultant force.
to get the length of the resultant force ⇒ use the cosines law
The cosine law is a² = b² + c² - 2 * b * c * cos (∠A)
Applying at the question where b = F₁ , c = F₂ and ∠A = ∠x
Given that F₁ = 100 pounds , F₂ = 150 pounds and ∠x = 180° - 40° = 140°
∴ (Resultant force)² = 100² + 150² - 2 * 100 * 150 * cos (∠140) = 55481
∴ Resultant force = √55481 = 235.54 ≅ 236 pounds
The answer is option 4 ⇒ 236 lb.
Hello, when x tends to
the term with the highest degree will lead the behaviour.
In other words.
![\displaystyle \lim_{x\rightarrow+\infty} {x^4+3x^3-2x+7}\\\\=\lim_{x\rightarrow+\infty} {x^4}\\\\=+\infty\\\\\\\displaystyle \lim_{x\rightarrow-\infty} {x^4+3x^3-2x+7}\\\\=\lim_{x\rightarrow-\infty} {x^4}\\\\=+\infty](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Clim_%7Bx%5Crightarrow%2B%5Cinfty%7D%20%7Bx%5E4%2B3x%5E3-2x%2B7%7D%5C%5C%5C%5C%3D%5Clim_%7Bx%5Crightarrow%2B%5Cinfty%7D%20%7Bx%5E4%7D%5C%5C%5C%5C%3D%2B%5Cinfty%5C%5C%5C%5C%5C%5C%5Cdisplaystyle%20%5Clim_%7Bx%5Crightarrow-%5Cinfty%7D%20%7Bx%5E4%2B3x%5E3-2x%2B7%7D%5C%5C%5C%5C%3D%5Clim_%7Bx%5Crightarrow-%5Cinfty%7D%20%7Bx%5E4%7D%5C%5C%5C%5C%3D%2B%5Cinfty)
So, the answer B is correct.
Thank you.